2013
DOI: 10.3744/jnaoe.2013.5.3.404
|View full text |Cite
|
Sign up to set email alerts
|

Towed underwater PIV measurement for free-surface effects on turbulent wake of a surface-piercing body

Abstract: ABSTRACT:In the present study, a towed underwater particle image velocimetry (PIV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Yao et al [46] applied PIV to determine the turbulence created by a grid placed inside a free surface channel. Seol et al [47] used towed underwater PIV to determine the water vertical and horizontal velocity fields behind a floating body, in order to characterize the turbulent wake and the influence that free surface has on it. To demonstrate that image velocimetry can be successfully used to characterize relatively large free surface flows (like rivers), Muste et al [48] performed laboratory measurements on a 3.4 m wide and approximately 23.5 m long free surface channel combining PIV with controlled surface wave image velocimetry in order to adapt the management of sediments at a river water intake.…”
Section: Assessment and Analysis Of Behavioral Barriersmentioning
confidence: 99%
“…Yao et al [46] applied PIV to determine the turbulence created by a grid placed inside a free surface channel. Seol et al [47] used towed underwater PIV to determine the water vertical and horizontal velocity fields behind a floating body, in order to characterize the turbulent wake and the influence that free surface has on it. To demonstrate that image velocimetry can be successfully used to characterize relatively large free surface flows (like rivers), Muste et al [48] performed laboratory measurements on a 3.4 m wide and approximately 23.5 m long free surface channel combining PIV with controlled surface wave image velocimetry in order to adapt the management of sediments at a river water intake.…”
Section: Assessment and Analysis Of Behavioral Barriersmentioning
confidence: 99%
“…For a single towing carriage run, 250 particle image pairs were acquired and Reynolds averaged to derive two in-plane components of the average velocity, two normal components of the Reynolds stresses, and one shear component. An uncertainty assessment of the PIV system, based on the uniform flow results (Seol et al, 2013), is reported in Table 1.…”
Section: Testing Facility Equipment and Data Acquisitionmentioning
confidence: 99%
“…(Gui, et al, 2001), 파랑 중에 놓인 동일 모형의 위상별 선미 유동장 계 측 (Longo, et al, 2007), 수면 관통 물체 주위의 유동장 계측 (Seol, et al, 2013)이 수행되었다. 그리고 두 대의 카메라를 이용해 2차원 평면의 3차원 속도 성 분을 얻어낼 수 있는 스테레오스코픽 입자영상유속계(sereo prticle iage vlocimetry, SPIV)가 예인수조에 도입되어 활용되었 다.…”
Section: 대한조선학회논문집 제 51 권 제 4 호 2014년 8월unclassified